2017
DOI: 10.1111/bjd.15513
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10-producing B-cells in autoimmune bullous diseases

Abstract: Linked Article: Kabuto et al. Br J Dermatol 2017; 176:1204–1212.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Studies have shown that there are a group of immunosuppressive B cells in a variety of autoimmune diseases [31,32], which are named "regulatory B cells," or Bregs for short [18][19][20]. Bregs can suppress the immune response by secreting cytokines of IL-10, TGF-β, and IL-35, etc., or regulate the immune response by interacting with the target cell membrane surface molecules of FasL, GITRL, and PD-L1 [33,34].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Studies have shown that there are a group of immunosuppressive B cells in a variety of autoimmune diseases [31,32], which are named "regulatory B cells," or Bregs for short [18][19][20]. Bregs can suppress the immune response by secreting cytokines of IL-10, TGF-β, and IL-35, etc., or regulate the immune response by interacting with the target cell membrane surface molecules of FasL, GITRL, and PD-L1 [33,34].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…7 However, the involvement of IL-10 and IL-35 in BP has not been reported yet. 8 In contrast, there are already reports that IL-10 levels are increased in pemphigus but not in BP. 9 Recently, the association between dipeptidyl peptidase-4 inhibitor (DPP4i) and BP has been well discussed.…”
mentioning
confidence: 94%
“…The possible role of IL‐35 in pemphigus has been reported 7 . However, the involvement of IL‐10 and IL‐35 in BP has not been reported yet 8 . In contrast, there are already reports that IL‐10 levels are increased in pemphigus but not in BP 9 .…”
Section: Introductionmentioning
confidence: 99%